Encapsulamento de aromas em micropartículas poliméricas naturais - Silva, Maíra Taynara Santos da (2018)
Biopolymers are usually biocompatible, biodegradable and non-toxic, presenting potential for the production of particles for use in humans. In particular, gelatine is a naturally occurring, low-cost and highly available protein and is therefore a promising material for the formation of microparticles in medical, pharmaceutical and food industry applications with a suitable degree of purification. Polysaccharides also stand out because they have similar properties. However, some materials obtained from such matrices have the disadvantage of high solubility in water, which limits the applications of the particles in aqueous media. Thus, the present work aims to study the use of non-toxic crosslinking agents and the effect of reaction time on the reduction of matrix solubility and encapsulation of aromas. The results showed that during the crosslinking time variations occur in dispersed phase viscosity, size and thermal resistance of the particles obtained from the reverse suspension reaction. It has been observed that the crosslinking agents may exert little or great influence on the final properties of the matrices studied and strongly depend on the reaction time. On the other hand, experimental data showed that the use of essential oils in the in situ encapsulation process can greatly influence the formation and morphology of the particles. The results of encapsulation efficiency indicated the presence of the compounds of interest, with increased encapsulation efficiency throughout the reaction.